2015
DOI: 10.1080/15504263.2015.1113842
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Counseling for Smoking Cessation in Smokers With Depressive Symptoms: A Randomized Controlled Pilot Trial

Abstract: This finding, while preliminary, suggests that an exercise and counseling intervention may yield better results than health education in improving smoking abstinence. This study is registered at www.clinincaltrials.gov under # NCT01401569.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
74
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(76 citation statements)
references
References 61 publications
1
74
0
1
Order By: Relevance
“…[7][8][9] Thus, designing effective smoking cessation interventions for women with depression-a tobacco use disparity group-is a public health priority. 10,11 Few studies targeted smokers with current depression [12][13][14][15][16][17] and only one of these targeted women specifically. 12 This pilot study evaluated the potential role of supervised vigorous exercise as a smoking cessation intervention for depressed females.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] Thus, designing effective smoking cessation interventions for women with depression-a tobacco use disparity group-is a public health priority. 10,11 Few studies targeted smokers with current depression [12][13][14][15][16][17] and only one of these targeted women specifically. 12 This pilot study evaluated the potential role of supervised vigorous exercise as a smoking cessation intervention for depressed females.…”
Section: Introductionmentioning
confidence: 99%
“…21 Moreover, two studies of exercise counseling encouraging home-based, unsupervised exercise for depressed smokers found no effect on smoking abstinence compared with a health education contact control group. 12,13 A supervised exercise program has the potential to benefit depressed smokers by providing reinforcement, guidance, and support for exercise; thus improving adherence. 18 As an initial step, we examined if the same effective intervention tested among women smokers 19 could also be efficacious for female smokers with depression, as individuals with psychiatric disorders including depression are understudied in the exercise for smoking cessation treatment literature.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been argued that exercise as a cessation aid, given its antidepressant and mood enhancing effect (Carek et al, 2011; Cooney et al, 2013; Dunn et al, 2005), may be particularly effective for smokers with elevated depressive symptoms (Bernard et al, 2013). Several preliminary studies with depressed smokers have found that aerobic exercise as an intervention may increase likelihood of smoking cessation outcomes (Bernard et al, 2015, 2012; Patten et al, 2016; Vickers et al, 2009). However, as is the case with the general population, adherence to exercise programs among smokers is low (Ussher et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A study on exercise and counselling for smoking cessation for those with current depressive disorders reports attrition rates of 20 % and 37 % for the intervention and control respectively [42]. Another exercise counselling for smoking cessation among depressed women [43] reports slightly higher attrition rates of 35 % at 10 weeks with no difference between arms.…”
Section: Introductionmentioning
confidence: 99%